THE URGENCY OF ISLAM TOWARD THE EPISTEMOLOGY OF QUANTUM SCIENTIFIC - Nurkhalis, Nurkhalis (IAIN Tulungagung, 2018)
The development of modernity has caused a clash of epistemology. Epistemology cannot be separated from evaluation, normative or critical discipline.Epistemology will often fall into subjectivity principles based on individual freedom. The existence epistemology of Islam is more on the problem of harmonious integration and synthesis between God’s and human knowledge or another term correlation of sharia and reason. Scientific epistemology includes two forms namely descriptive and normative. Normative scientific epistemology as an ordinary epistemic assessment, while descriptive scientific epistemology, which is constantly practicing making epistemic judgments or formulating epistemic systems as an assessment. This paper examine about the existenceof Islamic epistemology in relation to quantum scientific. This study involve avariety of disciplines ranging from Arabic grammar (nahwu, sharf, mantiq),interpretation, fikih, tauhid and tasawuf, social science, physical sciences,psychology science, medical science, geography science, biological science with proof through laboratories, telescopes and microscope.